Endoscopic far-lateral supracerebellar infratentorial approach for resection of posterior clinoid meningioma: Case report and literature review - Bai, Yang; Han, Song; Sun, Xiaoyu; Liu, Xuantong; Li, Xinning; Feng, Sizhe; Liang, Guobiao (Frontiers in Oncology, 2023)
Introduction The surgery of posterior clinoid meningioma (PCM) remains one of the most formidable challenges for neurosurgeons because of its location at great depth in the cranium and proximity to vital neurovascular structures. Herein, we aim to describe the technique and feasibility of a novel approach, the purely endoscopic far-lateral supracerebellar infratentorial approach (EF-SCITA), for resection of this extremely rare entity. Case description A 67-year-old women presented with gradually deteriorating vision in right eye for 6 months. Imaging examinations revealed a right-sided PCM, and the EF-SCITA approach was attempted for tumor resection. Tentorium incision allowed a working corridor toward the PCM in the ambient cistern through the supracerebellar space. During surgery, the infratentorial part of the tumor was found to compress the CN III and posterior cerebral artery medially and encase the CN IV laterally. Following debulking of the infratentorial tumor, the supratentorial part could be exposed and then excised, which had dense adhesions to the ICA and the initial part of the basal vein in front. After total tumor removal, its dural attachment was detected at the right posterior clinoid process and then coagulated under direct vision. The patient on follow-up at 1 month had improvement in visual acuity in right eye, with no restriction of extra-ocular movements. Discussion EF-SCITA approach combines advantages of the posterolateral approach and endoscopic technique, allowing access to PCMs with seemingly low risks of postoperative morbidity. It would be a safe and effective alternative for resection of lesions in the retrosellar space.